Incidence and characteristics of acute aortic dissection in patients with out-of-hospital cardiopulmonary arrest evaluated by non-contrast computed tomography. Issue 3 (October 2020) - Takeuchi, Shinsuke; Yamaguchi, Yoshihiro; Soejima, Kyoko; Yoshino, Hideaki
Background: The exact epidemiology of acute aortic dissection, including cases of out-of-hospital cardiopulmonary arrest, is unclear. We aimed to investigate the incidence and characteristics of acute aortic dissection in patients with out-of-hospital cardiopulmonary arrest transferred to our institution and validate the related factors to out-of-hospital cardiopulmonary arrest in Stanford type A acute aortic dissection. Methods: We retrospectively reviewed the acute-phase computed tomography data of patients with out-of-hospital cardiopulmonary arrest who visited our hospital between 1 January 2015 and 31 December 2017. Results: Among 1011 consecutive patients with out-of-hospital cardiopulmonary arrest, excluding those aged 17 years and younger and exogenous out-of-hospital cardiopulmonary arrest, such as suicide and trauma, 934 underwent computed tomography examination and 71 (7.6%) were diagnosed with acute aortic dissection: 66 with Stanford type A and five with type B acute aortic dissection (out-of-hospital cardiopulmonary arrest group). Seventy-five patients without out-of-hospital cardiopulmonary arrest with Stanford type A acute aortic dissection visited our institution during the same period (non-out-of-hospital cardiopulmonary arrest group). Age, incidence of massive bloody pericardial effusion and massive intrathoracic haemorrhage were significantly higher in the out-of-hospital cardiopulmonary arrest than in the non-out-of-hospital cardiopulmonary arrest group (78 ± 8 years, 72.7% and 24.2% vs. 70 ± 13 years, 26.7% and 1.3%, respectively; all P  < 0.01). These variables were independently related to out-of-hospital cardiopulmonary arrest. Conclusions: There may be more patients with acute aortic dissection with out-of-hospital cardiopulmonary arrest than previously thought. Aortic rupture into the pericardial space or thoracic cavity is the major cause of out-of-hospital cardiopulmonary arrest in these cases. Non-contrast computed tomography can be used to diagnose acute aortic dissection in patients with out-of-hospital cardiopulmonary arrest. Our study is one of a few to evaluate the real circumstances surrounding acute aortic dissection and its epidemiology.